Análisis Financiero a la Empresa Comercial “PAÑALERA BABYSHOP” de Claudia Carolina Luzuriaga Flores de la Ciudad de Loja, Periodo 2021-2022. - Bao Encalada, María Fernanda (2024)
The Curricular Integration Work called: Financial Analysis of the Commercial Company "Pañalera BabyShop" of Claudia Carolina Luzuriaga Flores of the City of Loja, Periods 2021-2022, has the purpose of evaluating and analyzing which is the economic- financial situation that the company went through in the periods studied, fulfilling the objectives set, through the execution of the vertical and horizontal analysis, as well as the application of financial indicators to make corrective decisions for the administrative and financial improvement of the company. In order to comply with the established objectives, it was based on a mixed approach methodology, that is, qualitative and quantitative. The qualitative approach was employed at the time of compiling, expanding and interpreting the relevant information both in the theoretical framework and in the results, where the following methods were used: scientific, deductive, inductive, analytical and synthetic, and the quantitative approach was employed at the time of obtaining the numerical data obtained from the application of the vertical and horizontal analysis, as well as the financial indicators in the basis of the company's financial- economic information, where the mathematical and statistical method was used. For the execution of the first objective, the financial information was compiled, where the restructuring of the Statement of Financial Position and the Income Statement for the three periods to be analyzed was carried out, after that, the vertical analysis was performed, which shows that the company has a high proportion of current assets, especially in inventories and financial assets, and that its costs are very high, which generates a low profitability. The horizontal analysis reveals that the company increased its inventories and sales in the period 2021, however, the net income for the period was lower, while in the period 2022, it reduced its inventories and therefore increased its income level. Subsequently, to meet the second objective, financial indicators were applied to evaluate its financial situation and performance, where it is highlighted that the company has good liquidity in 2020 and 2022 year, but high indebtedness in the 2021 period, which makes it difficult for it to meet its short-term obligations. It is also noted that the company pays its suppliers faster than it collects from its customers, which affects its cash flow. Finally, it is signaled that the company's profitability is regular in the three periods, due to its high operating costs. Finally, to meet the last objective, a financial analysis report was prepared, which presents a synthesis based on the results obtained from the financial-economic situation.